(3GdJcedI dhajGJ GdfbdIs - (3YHO GdYXje Hf YHO Gdbhj Hf YHO Gddg, CHh eMeO, Rcj GdOjf GdefPQj ,J (B656 (3g` s
(3ChdgG (B:s
(3ai GdQGHY ef GdeMQe Jhai GdTjN GdCLd CHh efUhQ CMeO Hf GdTjN GdCLd CHj TLGY jMji Hf CMeO Hf Ydi Hf eMeO Hf GdHQGM GdHZOGOi Gdhcjd GdUhai s
(3BNQgG (B:s
(3hJhai QVi Gddg Yfg ai jhe GdSHJ Chd GdSGYI GdYGTQI ef GdfgGQ GdePchQ QGHY Pi GdbYOI hYdi GdeSdejf ef HQcI ai GdOfjG hGdBNQg Bejf s
(3HChdg JedcGf heWGdYI eDQNI SfI (B834(3g`s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B30s
(3eUOQ GbJfGA GdCUd (B:s
(3GdeJMa GdHQjWGfi s
Keywords: (3GdJGQjNs